The Content of Lactic Acid and Lactose of Yoghurt Fermented with Different Number and Percentage Starter Bacteria - Prayitno, Prayitno (ANIMAL PRODUCTION, 2006)
The objective of the research was to study rate of lactose fermentation and production of lactic acid  by  Streptococus  thermophillus and Lactobacillus  bulgaricus. Yoghurt  was  made from  skim milk 10 percent  inoculated  with  Streptococus  thermophillus and  Lactobacillus  bulgaricus different number  and  percentage.  The  research  was conducted  in a completely  randomzed design factorial  pattern  3 x 4.  The  first  factor was  different (R) of  Strepcocus  thermophillus and Lactobacillus  bulgaricus 109 : 109 (1 : 1), 109 : 2x109 (1 : 2)  and 2x109 : 109 (2 : 1), and second factor was  percentage (S)  of starter, with  were  1, 2, 3  and  4 percent.  Each  treatment  has three replicated.  Variabels  measured  ware lactic acid  and  lactose content  of yoghurt after  12 hours  fermented.  Lactic acid content  was determined   by titration  and lactose  content by  spectrofotometry.  Result  showed that number  of Streptococus thermophillus and Lactobacillus  bulgaricus and percentage  of starter, including  ther  interaction, have  very hight  significant  (P<0,01) affect  on  lactic  acid and  lactose  content  of yoghurt.   For  resulted  the yoghurt  with  the best  quality (midle   of  lactic  acid  and  lower lactose content) recommended  to used  Streptococus  thermophillus and  Lactobacillus  bulgaricus 1 : 2 with  4 percent  starter  addition. (Animal Production 8(2): 131-136 (2006) Key Words  : Streptococus thermophillus, Lactobacillus bulgaricus, starter, yoghurt, lactic acid, lactose